Creation of an α-mannosynthase from a broad glycosidase scaffold. - Yamamoto, K; Davis, B (2012)
α-Mannosides made easy: Mutation of a family-GH31 α-glucosidase that displays plasticity to alterations at the 2-OH position of donor substrates created an efficient α-mannoside-synthesizing biocatalyst. A simple fluoride donor reagent was used for the synthesis of a range of mono-α-mannosylated conjugates using the α-mannosynthase displaying low (unwanted) oligomerization activity. Copyright © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.